Atrioventricular Sequential Pacing for Hypertrophic Cardiomyopathy During Liver Transplantation. Issue 8 (15th October 2015) - Ramos, Juan; Pai, Sher-Lu; Perry, Dana K.; Blackshear, Joseph L.; Aniskevich, Stephen
Abstract : Hypertrophic cardiomyopathy is a myocardial disorder that carries an increased risk of morbidity and mortality during liver transplantation. We describe the use of atrioventricular sequential pacing, placed preoperatively, to assist with intraoperative management of a patient with severe refractory hypertrophic cardiomyopathy undergoing orthotopic piggyback liver transplantation. We discuss the pathogenesis and treatment of this infrequent but serious comorbidity. Abstract : Supplemental Digital Content is available in the text.